2011
DOI: 10.5862/mce.22.5
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of Fillet-welded Joint Assessment by the FEA Simulation of Damage Accumulation

Abstract: Fatigue strength evaluation of non-continuous incomplete penetration fillet-welded joints transferring stress flow by the S-N criteria incorporating the «Hot-spot stress» or «Notch-stress» approaches is dubious since the characteristic stress at the crack initiation location is not established by the rules for fatigue design. Application of the linear fracture mechanics (LMF) technique meets a problem of numerical modeling the crack three-dimensional shape and front extension, which becomes insoluble when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Considered approach is based on the damage accumulation technique proposed by Glinka et al and Ellyin et al , which later became widespread, e.g. for the two‐dimensional fatigue cracks modelling . The main advantage of this approach is that the crack initiation and propagation stages are not separated and considered as a single process controlled by the gradual damage accumulation.…”
Section: Fatigue Estimation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Considered approach is based on the damage accumulation technique proposed by Glinka et al and Ellyin et al , which later became widespread, e.g. for the two‐dimensional fatigue cracks modelling . The main advantage of this approach is that the crack initiation and propagation stages are not separated and considered as a single process controlled by the gradual damage accumulation.…”
Section: Fatigue Estimation Methodologymentioning
confidence: 99%
“…for the two-dimensional fatigue cracks modelling. 22 The main advantage of this approach is that the crack initiation and propagation stages are not separated and considered as a single process controlled by the gradual damage accumulation. It is not necessary to have the initial defect for the crack nucleation; local material heterogeneity can be a crack source.…”
Section: Finite Element Modellingmentioning
confidence: 99%
“…There are few studies on this aspect, especially on the interface influence coefficient. A review of the literature revealed that many metal materials and composite materials conform to a Weibull distribution (Cao et al, 2004;Han and Ga, 2019;Wang T. S. et al, 2022;Wang Z. J. et al, 2022;Wu, 2022) and a lognormal distribution (Zeng and Yu, 1991;Wang et al, 2019) in a fatigue damage stage (Guchinsky and Petinov, 2011;Petinov et al, 2016). Therefore, damage variable factor D is introduced in this paper and assumed to be a function related to interface displacement.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that it be used to examine the onset of cracks in cavities and the progress of cracks in the joint of discontinuous T-Bar profiles [15]. The starting point of the crack is a hole and a three-dimensional shape, and its development is simulated and enters the plastic elastic region of the weld metal until complete failure of the weld occurs [16]. Performed fatigue tests in three methods and the plate's direction with a welded joint are under bending load [17].…”
Section: Introductionmentioning
confidence: 99%